The Effectiveness of Behavioral Cognitive Mentoring: A Model in Reducing Psychological Stress between Mothers of kids with Cerebral Palsy - Bakar, Norsuhaily Abu; Bakar, Norsuhaily Abu; Al-Smadi , Mohammad Shaban; Hassan, M.S.N. Abu (International Journal of Psychosocial Rehabilitation, 2020)
The birth of a newborn child brings with it shifts in the family’s structure and adds up to the parents ’ obligations. Families want a child with a common ideal. Furthermore, the opposite occurs in which parents sometimes have a disabled child that can impact the family, resulting in the distress of parents from psychological stress that needs professional assistance from clinicians and counselors. The purpose of this study is to investigate the impact of cognitive-behavioral therapy (CBT) on psychological stress management for mothers of children with cerebral palsy (CP). Cognitive Behaviour Therapy could be an essential part of the intervention used to reduce parenting Stress between Mothers of kids with Cerebral Palsy. We suggest a pragmatic conceptual model designed to clarify the process of development expectations, in order to inform future research into the measurement of health expectations and to enhance our understanding of the aspects influencing the expectations on health behavior and attitudes.